Stretch Forming of Sheet Metal. A Review of Some Instability Theories and The Design and Construction of A Testing Rig For Formability Studies of Thicker Guage Materials - Paul-Chowdhury, Sisir R. (My University, 1974)
Some instability theories relating to the stretch forming of sheet metal are reviewed, and a comprehensive computer programme based on Marciniak's modified mathematical model is developed to determine, theoretically, the Forming Limit Diagram. Also, Kasper's Shape Analysis technique is analyzed in the form of an Optimization model, and an attempt is made to correlate it with the theoretically determined FLD in order to predict the formability of sheet metal in advance. At the same time, a testing rig is designed, built and tested for the determination of the FLD of thicker guage materials under laboratory conditions.
Keywords: Mechanical Engineering; Mechanical Engineering